The Contribution of Submarine Optical Fiber Telecom Cables to the Monitoring of Earthquakes and Tsunamis in the NE Atlantic - Matias, Luis; Carrilho, Fernando; Sá, Vasco; Omira, Rachid; Niehus, Manfred; Corela, Carlos; Barros, José; Omar, Yasser (Frontiers in Earth Science, 2021)
Recent developments in optical fiber cable technology allows the use of existing and future submarine telecommunication cables to provide seismic and sea level information. In this work we study the impact of three different technologies, i) SMART, Science Monitoring and Reliable Telecommunications; ii) DAS, Distributed Acoustic Sensing, and; iii) LI, Laser Interferometry, for effective earthquake and tsunami monitoring capabilities on the NE Atlantic. The SW Iberia is the source area of the largest destructive earthquake that struck Europe since the year 1000, the 1st November 1755 event. This earthquake generated also a destructive tsunami affecting the whole basin. This tectonically active area is crossed by the CAM (Continent-Azores-Madeira) submarine cable on a ring configuration. Due to the end of cable lifetime the current cables need to be replaced by 2024 and the technical requirements must be defined in mid-2021. The Azores archipelago is the focus of frequent seismic crises and occasionally destructive earthquakes. A common feature of these seismic events is that they take place offshore, an area that is difficult to monitor from land-based instruments. In this work we evaluate the contribution of SMART cables to the earthquake monitoring and tsunami early warning system in SW Iberia and show how DAS and LI can improve earthquake monitoring on two active domains of the Azores. For tsunami early warning we show how the offshore sea-level measurements provide clean offshore tsunami records when compared to coastal observations by tide gauges, which greatly improves the efficiency of the system. For earthquake monitoring, the data processing operational routine is examined using Monte-Carlo simulations. These take into consideration the errors in phase picking and the uncertainty on the 1D velocity model used for earthquake location. Quality of earthquake location is examined using the difference between true and the centroid of the computed epicenters and by the overall ellipse of uncertainty obtained from 100 runs. The added value provided by instrumented submarine telecommunication cables to mitigate earthquake and tsunami risk demonstrated in this work will help authorities and the society in general to take the political decisions required for its full implementation worldwide.